A Penatalaksanaan Holistik Penyakit Tuberkulosis Paru dengan Gout Arthritis pada Wanita Usia 41 Tahun Melalui Pendekatan Kedokteran Keluarga - Betari Ariefia; Azelia Nusadewiarti (Medula, 2021)
Indonesia is the second country with the highest incidence of TB cases in the world in 2020. New TB cases in Indonesia is 543,874 cases in 2020 (20 March 2020). Meanwhile, there were 777 new TB cases in Lampung province (June 2020). The increase in TB infection is influenced by several factors, age, gender, nutritional status, level of cleanliness, ventilation, temperature, lighting, occupant density, and education. Gout arthritis is an inflammatory joint disease that is influenced by the intake of high-purine foods or other factors such as anti-tuberculosis drugs. Pyrazinamide can inhibit uric acid excretion in the kidneys and increase the value of blood uric acid. Therefore, it takes the role of a family doctor who can manage patients from various aspects. The aim of research is to apply a holistic and comprehensive family doctor approach in detecting internal and external risk factors and solving problems based on Evidence Based Medicine which is family-approached and patient-centered. This study is a case report. Primary data from autoanamnesis, physical examination, and home visits. Secondary data from patient medical records. The patient has functional grade 2 in pulmonary TB disease and Gout Arthtitis with internal risk factors, the patient's lack of knowledge of the disease and curative treatment behavior; External factors are low income families, home environment is close to dusty and slum areas. The intervention are education for control according to schedule, cough ethics and TB transmission, and low-purine diet. In the evaluation there are changes in the patient's behavior and diet.